Humanities and Social Sciences Undergraduates’ Perspectives about the Medium of Instruction in the Degree Programmes Offered at the State Universities in Sri Lanka - Ariyasinghe, D.A.G.; Ariyasinghe, N.P.G. (University of Jaffna, 2025)
In both academic and corporate sectors today, there is an increased demand for both competency and fluency in the English Language. To address this development, aligning with the changes in the higher education sector in the world, a significant number of degree programmes in Sri Lankan universities are also being streamlined in the process of internationalisation and are offered in the English medium. In disciplines such as applied sciences, medicine, technology, and management, almost all degree programmes are mostly offered in the English Medium. However, the degree programmes in the disciplines of humanities, social sciences, and fine arts are predominantly offered in either Sinhala or Tamil. Thus, considering the above context, the present study is conducted to investigate the humanities and social sciences undergraduates’ perspectives on the medium of instruction in their respective degree programmes. In this mixed-method research study, a trilingual questionnaire representing Sinhala, Tamil and English was circulated among the participants to collect data. The questionnaire is designed to elicit their responses to the medium in which they currently receive instruction in their degree programmes as well as the challenges they would anticipate in instances when it changes to English. Especially, in terms of the students who are currently learning under the EMI (English-Medium Instruction), it strives to explore the challenges faced while comprehending the lecture materials and facing assessments and evaluations, besides their prospective suggestions to support the students to eliminate language barriers. Conclusively, it is believed that the present study will remedy the existing dearth of studies that have been conducted concerning the medium of instruction in the undergraduate programmes in humanities and social sciences, within the Sri Lankan state university system.
Keywords: Humanities; Medium of Instruction; Social Sciences; Sri Lankan Universities